Spatial and temporal heterogeneity of runoff and soil loss dynamics under simulated rainfall - SzabóJudit; Jakab, Gergely; Szabó, Boglárka (Hungarian Geographical Bulletin, 2015)
The factors affecting soil erosion processes are complex and various, comprises two phases: detachment and transport by water. Previous studies indicated that initial moisture content, slope and soil crusts are playing an important role in soil erosion. The primary objectives of this study were to examine the sediment concentration and aggregate size distribution of the washed sediment. Aims were also to create different season specifically modelled situations in order to check runoff rates on bare soils under heavy rainfall. The experiments were conducted with a laboratory-scale rainfall simulator using a 1/2 HH 40 WSQ fulljet nozzle on eutric calcaric Cambisol loamic. Altogether, 72 soil loss samples were collected (6 separate precipitations, 3 time periods, 4 particle size fractions). The experiments indicated that the runoff rate was not increased by the presence of soil crusts, and even less sediment occurs on crusted surfaces. This sediment contained smaller fractions compared to recently tilled surface. The sediment concentration increased with the slope angle, but the runoff rates probably depend rather on the micro-morphology and initial moisture content of the surface. The main erosion process is the raindrop erosion after inland inundation and drought in gentle slopes, while the intermediate period of the precipitation is the most erosive. In general, the ratio of the macro aggregates in soil losses decrease and the ratio of the smaller fractions increase with the time during a precipitation event. Changing climate conditions are shown to have an effect on agricultural production through the temporal and spatial distribution of the erosion rates.